Adapted Acoustic CR Neuromodulation in Patients With Chronic Tonal Tinnitus and Hearing Loss - Wurzer, Hannes; Hauptmann, Christian (Frontiers in Medicine, 2018)
Chronic tonal tinnitus is often accompanied by sensorineural hearing loss which is associated with altered tuning curves and bandwidth of alternating masking. In this feasibility study the so-called hearing threshold adapted coordinated reset (HTA-CR) neuromodulation was investigated. This method is based on CR neuromodulation, which is an effective treatment for chronic tonal tinnitus. It applies four stimulation tones that are determined by the patient’s individual tinnitus frequency and hearing impairment. 25 patients used the DesyncraTM for Tinnitus Therapy System programmed for HTA-CR neuromodulation for four months on average, and applied the treatment four hours daily. Regular check-ups were done every 4 – 6 weeks. Therapy outcome was assessed by the tinnitus questionnaire (Tinnitusfragebogen, TF) as per Goebel and Hiller. After 4 months the mean TF score was reduced by 27.4%. 40% of the patients showed a reduction of ≥ 15 points while for further 32% of the patients a reduction of 6 – 14 points was found. Thus, a remarkable response rate of 72% was observed after only 4 months of HTA-CR neuromodulation. Our results suggest that HTA-CR neuromodulation might be at least comparable to standard CR neuromodulation providing another effective therapeutic option in the treatment of chronic tonal tinnitus.